Improved Survival From Graft-versus-host Disease Following Pediatric Small Intestinal Transplantation Through Reduction in Systemic Immunosuppression Altering T-cell Chimerism Dynamics - Sandeep Potluri, FRCPath, PhD; Sarah Lawson, FRCPath; Shyla Kishore, FRCPCH; Malobi Ogboli, FRCP; Jane Hartley, FRCPCH; Arun Alfred, FRCPath; Yvonne Wilson, FRCSG (Plast); Darius F. Mirza, FRCS; Khalid Sharif, FRCS; Girish Gupte, FRCPCH (Transplantation Direct)
Background. Graft-versus-host-disease (GvHD) is an infrequent but serious complication of small intestinal transplantation in children, which is associated with a very poor prognosis. This study evaluated a novel strategy of managing GvHD in these patients through a reduction in immunosuppression. Methods. We conducted a retrospective review 108 consecutive pediatric patients at our center between 2005 and 2021, who had small intestinal transplantation. We assessed clinical features and outcomes as well as laboratory chimerism studies in cohorts of patients before and following a change in treatment strategy for GvHD from intensification to reduction in immunosuppression. Results. Fourteen percent of pediatric patients developed GvHD after small intestinal transplantation. A change in treatment strategy to a reduction in immunosuppression led to significantly improved overall survival (log rank P = 0.015). This improved survival correlated biologically with altered T-cell chimerism dynamics in blood; in patients who had a reduction in immunosuppression, there was abrogation of the rise in donor T-cell chimerism over time seen in the blood of patients who instead had intensification of their immunosuppression. This may be because of permitting recipient lymphocytes to have a host-versus-graft effect and outcompete donor-derived lymphocytes. Conclusions. Our results demonstrate that that altering the immunosuppressive therapy strategy, following clinical manifestations of GvHD such as a typical skin rash, from intensification to a reduction in immunosuppression led to significantly improved survival.